Portable Pedal Powered Washing Machine - Mohd Khairy, Muhammad Zul'Akmal; Roslan, Muhammad Zulfadhli; Khairul Anwar, Muhammad Hamdi; Mohamad, Mahmod Abd Hakim; Onn, Nurfarahin; Ismail, Suhairi; Kadis, Ghazali (Multidisciplinary Applied Research and Innovation, 2026)
Access to affordable and sustainable laundry solutions remains a significant challenge in off-grid regions and resource-constrained environments. Conventional washing machines are energy-intensive and expensive, while traditional manual washing is physically taxing and time-consuming. This study details the design and development of a portable pedal-powered washing machine, utilizing recyclable materials and an ergonomic structure to enhance user accessibility. The methodology involved mechanical design optimization followed by a comparative performance analysis against manual washing methods. Results indicate that the prototype effectively reduces physical strain and operational costs while maintaining cleaning efficiency without electrical dependency. Ultimately, this machine serves as a viable, eco-friendly alternative that promotes sustainable living and improved user well-being in diverse populations.